2020
DOI: 10.1080/14992027.2020.1817993
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory investigation of speech recognition thresholds in noise with auralisations of two reverberant rooms

Abstract: Objective: Speech-in-noise tests are widely used in hearing diagnostics but typically without reverberation, although reverberation is an inextricable part of everyday listening conditions. To support the development of more real-lifelike test paradigms, the objective of this study was to explore how spatially reproduced reverberation affects speech recognition thresholds in normal-hearing and hearingimpaired listeners. Design: Thresholds were measured with a Finnish speech-in-noise test without reverberation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…They also assigned an additional task that had the participants guess which category the sentence belonged in out of a total of 20 sentences grouped into two categories (short and long RT conditions). Kuusinen et al (2020) [29] also found no significant difference in speech recognition thresholds influenced by reverberation. The discrepancy might be originated from source-listener distance (typically 1 m).…”
Section: Discussionmentioning
confidence: 93%
“…They also assigned an additional task that had the participants guess which category the sentence belonged in out of a total of 20 sentences grouped into two categories (short and long RT conditions). Kuusinen et al (2020) [29] also found no significant difference in speech recognition thresholds influenced by reverberation. The discrepancy might be originated from source-listener distance (typically 1 m).…”
Section: Discussionmentioning
confidence: 93%
“…Unfortunately, the situation deteriorates significantly for those with hearing problems, including the aging population [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Harris and Swenson assessed speech intelligibility for people with and without sensorineural hearing impairment in three acoustic environments [ 33 ].…”
Section: Introductionmentioning
confidence: 99%